Still waters run deep - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Wetlands are highly productive areas, offering a home to many plant and animal species and being a major storeroom for the world s water, oxygen and carbon dioxide. Among the competing claims of production, profit and preservation, what is the...